Analysis of the Performance of Koasi K01A Public Transport During the Implementation of the PSBB - Muhammad Isradi; Muhammad Abdika Abdika (NAROTAMA UNIVERSITY, Indonesia)
This research shows that the average number of passengers during the implementation of the PSBB is reduced by 50%, although there are still some Koasi K01A whose number of passengers exceeds the health protocol standard recommended by the government. Respondents considered the feasibility of the K01A Koasi to operate as still quite feasible, because there were still some respondents who still needed this Koasi K01A to travel so that it could be judged that the K01A Koasi was still feasible to operate to serve its passengers, only had to replace the old Koasi units with a newer unit that provides comfort for Koasi K01A passengers. The comfort and safety provided by the K01A Koasi manager are still considered very uncomfortable and safe by respondents.